A silver deposit from Niedźwiedź – another premise in the study of the origins and function of a stronghold in steklin in Dobrzyń region - Chudziak, Wojciech; Musiałowski, Adam; Weinkauf, Marcin (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2023)
The article concerns an early medieval silver hoard, recently (and accidentally) discovered at a suburb settlement in Niedźwiedź in Dobrzyń region. The settlement is a part of a large complex with a stronghold and a developed lake shore, identified with the historical Steklin mentioned in the so-called Mogilno Falsification. The hoard, consisting of 28 coins and six pieces of jewelry, was deposited after 1080. The factual scope of the article includes primarily the results of numismatic analyses of one Arabic coin and the remaining Western European coins, including the prevailing group of so-called cross denarii. The discovery is interpreted in a broad socio-economic and political context